ANALISIS SISTEM PENJAMINAN MUTU PENDIDIKAN (SPMI DAN SPME) DALAM PERSPEKTIF KEBIJAKAN EVALUASI DAN MONITORING PENDIDIKAN DI INDONESIA - Melkior Wewe; Putu Kerti Nitiasih; Putu Nanci Riastini; Ni Nyoman Trisna Herawati (STKIP Pesisir Selatan, 2026)
Objective: This article analyzes the relationship between the Internal Quality Assurance System (SPMI) and the External Quality Assurance System (SPME) within Indonesia’s education evaluation and monitoring policy. Methods: A systematic literature review was conducted using the PRISMA 2020 framework. Articles were searched in ERIC and Scopus with keywords related to internal quality assurance, external quality assurance, school self-evaluation, inspection, accreditation, governance, and Indonesian education. From 100 initial records, 10 studies were included after identification, screening, eligibility assessment, and final selection. Data were analyzed through thematic synthesis. Results: The review produced four major themes: self-evaluation as the foundation of internal quality improvement, inspection and accreditation as external accountability instruments, the complementary relationship between SPMI and SPME, and implementation challenges in Indonesia’s institutional settings. Novelty: This study highlights that educational quality assurance should not be treated only as administrative compliance. Effective quality policy requires the integration of internal reflection and external verification into a continuous quality improvement cycle supported by data use, institutional capacity, stakeholder participation, contextual leadership, and sustainable improvement-oriented monitoring.